2021
DOI: 10.3389/fneur.2021.771034
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Frequency Repetitive Transcranial Magnetic Stimulation Restores Dynamic Functional Connectivity in Subcortical Stroke

Abstract: Background and Purpose: Strokes consistently result in brain network dysfunction. Previous studies have focused on the resting-state characteristics over the study period, while dynamic recombination remains largely unknown. Thus, we explored differences in dynamics between brain networks in patients who experienced subcortical stroke and the effects of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) on dynamic functional connectivity (dFC).Methods: A total of 41 patients with subcortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
5
2
Order By: Relevance
“…However, the brain's activity is inherently dynamic. This temporal dynamic variability is closely related to neural networks functionality and can reveal fluctuations in network interactions (Allen et al, 2014) and patterns of recurrent brain activity that are beyond the scope of static analyses (Liegeois et al, 2017;Qin et al, 2021). The findings of this study indicate that the dynamic neural properties metrics have greater potential than the static characteristics for diagnosing and predicting cerebral neurological function states in the stroke patients.…”
Section: Discussionmentioning
confidence: 81%
“…However, the brain's activity is inherently dynamic. This temporal dynamic variability is closely related to neural networks functionality and can reveal fluctuations in network interactions (Allen et al, 2014) and patterns of recurrent brain activity that are beyond the scope of static analyses (Liegeois et al, 2017;Qin et al, 2021). The findings of this study indicate that the dynamic neural properties metrics have greater potential than the static characteristics for diagnosing and predicting cerebral neurological function states in the stroke patients.…”
Section: Discussionmentioning
confidence: 81%
“…HF rTMS, LF-HF rTMS, LF rTMS long ITI rTMS, paired associative stimulation, or short ITI rTMS was associated with improved upper limb muscle synergies in 782 patients from 17 studies (SMD, 1.20 [95% CI, 0.73–1.68]; I 2 , 88%). 17–32…”
Section: Resultsmentioning
confidence: 99%
“…HF rTMS, LF-HF rTMS, LF rTMS long ITI rTMS, paired associative stimulation, or short ITI rTMS was associated with improved upper limb muscle synergies in 782 patients from 17 studies (SMD, 1.20 [95% CI, 0.73-1.68]; I 2 , 88%). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] There was no statistically significant effect of iTBS or LF rTMS on lower limb muscle synergies in 168 patients from 5 studies (SMD, −0.19 [95% CI, −0.80 to 0.42]; I 2 , 74%). 26,[33][34][35][36] HF rTMS, iTBS, or LF rTMS was associated with improved muscle strength in 261 patients from seven studies (SMD, 0.52 [95% CI, 0.04-1.00]; I 2 , 69%).…”
Section: Effects Of Rtms Within 3 Months After Stroke At the Level Of...mentioning
confidence: 99%
“…A recent study indicated that the changes in frontostriatal FC would accompany suicidality reductions following transcranial magnetic stimulation (TMS) in patients with comorbid post-traumatic stress disorder and depression (Barredo et al, 2021). Meanwhile, researchers have also found that low-frequency repetitive TMS can restore the dFC of sensorimotor and cognitive control domains in patients with subcortical stroke (Qin et al, 2021). Concordant with another study (Philip, Barredo, Aiken, & Carpenter, 2018), these findings may suggest that TMS modulates and potentially normalizes functional relationships between neural networks were associated with clinical improvement.…”
Section: Discussionmentioning
confidence: 99%